2005
DOI: 10.1002/nla.425
|View full text |Cite
|
Sign up to set email alerts
|

An implicit QR algorithm for symmetric semiseparable matrices

Abstract: The QR algorithm is one of the classical methods to compute the eigendecomposition of a matrix. If it is applied on a dense n x n matrix, this algorithm requires O(n 3 ) operations per iteration step. To reduce this complexity for a sytmmetric matrix to O(n), the original matrix is first reduced to tridiagonal form using orthogonal similarity transformations. Article information AbstractThe QR algorithm is one of the classical methods to compute the eigendecomposition of a matrix. If it is applied on a dense … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 32 publications
(41 reference statements)
0
27
0
Order By: Relevance
“…We know that the semiseparable structure will be preserved under a QR and RQ-iterations [17] and hence also under the rational method presented here. Nevertheless, it is worth trying to prove the preservation of the structure directly by investigating in detail the structure of the intermediate matrices.…”
Section: Preservation Of the Semiseparable Structurementioning
confidence: 92%
See 2 more Smart Citations
“…We know that the semiseparable structure will be preserved under a QR and RQ-iterations [17] and hence also under the rational method presented here. Nevertheless, it is worth trying to prove the preservation of the structure directly by investigating in detail the structure of the intermediate matrices.…”
Section: Preservation Of the Semiseparable Structurementioning
confidence: 92%
“…Any kind of structure can be considered such as Hessenberg [15,16], tridiagonal [2], band, Hessenberg-like [17], semiseparable, quasiseparable [18], unitary plus low rank [19,20,21], etc. 2 Similar to the QR-case one can prove that a step of the RQ-algorithm preserves the structure of the matrix A.…”
Section: Preservation Of the Structurementioning
confidence: 99%
See 1 more Smart Citation
“…Recently, many authors have been intrigued by hidden rank properties in dense matrices. Basic theoretical results on rank structured matrices [3,4], quickly evolved to system solvers for these matrices [5,6] and to eigenvalue methods based on these matrix structures [7,8,9]. 1 A companion matrix, which is Hessenberg, can be written as the sum of a unitary and a rank 1 matrix.…”
Section: Definition 1 Given a Monic Polynomial P(z)mentioning
confidence: 99%
“…The authors showed that the matrix U k can be written as a product of three sequences of 2 × 2 unitary transformations as represented in (7). The presented method is an explicit QR-algorithm, in which special compression is needed to maintain the unitary structure.…”
Section: Definition 1 Given a Monic Polynomial P(z)mentioning
confidence: 99%